TEKNIK AKROSTIK DALAM PEMBELAJARAN MENULIS GEGURITAN - Diena Oktafina Hanim; Darni; Dendy Andriyanto , Octo; Ahmadi, Anas (UNIVERSITAS PGRI YOGYAKARTA, 2025)
This study aims to examine the effectiveness of the acrostic technique in learning to write geguritan (Javanese-language poetry) through a literature review approach. Writing geguritan is an essential part of Javanese language learning, which not only aims to improve language skills but also to preserve local cultural values that are increasingly eroded by the passage of time. In practice, many students face difficulties in writing geguritan, particularly in selecting appropriate diction, understanding traditional poetic structures, and using proper and accurate krama (formal) Javanese. The acrostic technique, which has previously been widely used in learning to write poetry in Indonesian, is believed to be a viable alternative solution to address these challenges. This technique helps students express their ideas in a structured manner by using the initial letters of each line as a guide, making the writing process easier and more directed. This study analyzes seven previous studies that employed the acrostic technique in teaching poetry writing, both in the context of the Indonesian and Javanese languages. The results show that the acrostic technique is effective in enhancing students' poetry writing skills across various educational levels, fostering creativity, increasing learning motivation, and assisting students in composing poems systematically and meaningfully.